Littles: Affects and Aesthetics in Sexual Age-Play - Tiidenberg Katrin; Paasonen Susanna (My University, 2025)
This article explores the experiences and practices of self-identifying female sexual age-players. Based on interviews and observation of the age players’ blogged content, the article suggests that, rather than being fixed in one single position, our study participants move between a range of roles varying across their different scenes. In examining accounts of sexual play, we argue that the notion of play characterizes not only their specific routines of sexual “scening” but also sexual routines, experimentations, and experiences more expansively. Further, we argue that a focus on play as exploration of corporeal possibilities allows for conceptualizing sexual preferences and practices, such as age-play, as irreducible to distinct categories of sexual identity. The notion of play makes it possible to consider sexuality in terms of transformations in affective intensities and attachments, without pigeonholing various preferences, or acts, within a taxonomy of sexual identities. In doing so, it offers an alternative to the still prevalent categorical conceptualizations of sexuality that stigmatize people’s lived experiences and diminish the explanatory power of scholarly and therapeutic narratives about human sexuality.